Ceftazidime-avibactam for the treatment of multidrug-resistant or extensively drug-resistant bacteria infection in preterm infants: case series study and literature review - Guang, Shiqi; Sang, Tian; Ru, Xifang; Zhang, Xin; Feng, Qi; Wang, Ying; Li, Shan (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate efficacy and safety of ceftazidime-avibactam (CZA) in preterm infants with multidrug-resistant (MDR) or extensive drug-resistant (XDR) bacterial infections.MethodRetrospective analysis of clinical data was conducted on preterm infants who were monitored in NICU of Peking University of First Hospital for MDR/XDR infections between 2022 and 2025. A literature search was performed using PUBMED and WANFANG databases.ResultsSix preterm infants (median gestational age 26+3 weeks) received CZA treatment for MDR/XDR bacterial infections, including five bloodstream infections and one ventilator associated pneumonia. CZA was used as monotherapy in three patients and as combination therapy with colistin or aztreonam in three patients. The median postnatal age at treatment initiation was 31 days. Five patients achieved clinical cure without adverse effects (AEs). One patient with concurrent CNS infection did not complete the treatment due to onset of unexpected status epilepticus. The literature search retrieved 44 preterm infants or neonates using CZA for sepsis or focal infections. Clinical cure rate was 84.09% (37/44). The most frequent AEs included liver function abnormalities, increased serum creatinine, hypomagnesemia and thrombocytopenia which were reversible.ConclusionCZA alone or combined with aztreonam or colistin is effective and well-tolerated in critically ill preterm infants. However, the small sample size of patients limits the definitive conclusions about the safety profile of CZA, especially CNS risks. Further studies on the pharmacokinetics/pharmacodynamics and safety of CZA in preterm infants are warranted.